THE CONTRIBUTION OF ENTREPRENEURSHIP EDUCATION, ON THE JOB TRAINING EXPERIENCE AND UTILIZATION OF UNIT PRODUCTION ON ENTREPRENEURSHIP INTEREST OF VOCATIONAL SCHOOL STUDENTS - Yazel Aze, Hazevi Atila; Widihastuti, Widihastuti (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
The aim of this study is to reveals the contribution of entrepreneur education, On The Job Training experience and the utilization of unit production by respective and stimultaneously to entrepreneurship interest of SMKN Tourism Program Students in Padang city. The study used ex post facto approach and correlation method with 725 population consisted all of senior year student SMK N Padang in tourism program. This study sample was selected by using proportionate random sampling and reach 360 students. The data were collected by using questionnaire, while the instrument validity was assed by CFA method and for analize the data using descriptive and inferential statistic analize that is regression method. The result of this study shows that: (1) the contribution of entrepreneur education, On The Job Training experience and utilization of unit production variabel respectively are 2.9%, 4.7% and 6% and positively effected (2) the contribution of entrepreneur education, On The Job Training experience and utilization of unit production variabel simultaneously is 7.9% and positively affected.